Efektifitas Strategi Pembelajaran Analisis Nilai Terhadap Pengembangan Karakter Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam - Abdullah, Usep Mudani Karim; Azis, Abdul (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2019)
This article aims to determine the differences in character between students using the value analysis learning strategy by not using the value analysis learning strategy. In value education there are various approaches, one of which is the value analysis approach. Learning strategies of value analysis in the learning of Islamic Cultural History feature stories and stories. The research method used is experimental research. The results of this study indicate that the control class that does not use the learning strategy of value analysis can be seen from the mean value (average) which is 89.04, including the low category. Then, the experimental class that uses the learning strategy of value analysis can be seen from the mean (average) which is 112.57 including the medium category. The test results of the control class and experimental class can be seen from the value of sig. (2-tailed) 0,000 <0.05, it can be concluded that the experimental testing between the control class and the experimental class was successful.